Marked : a Mindspace Investigations novel - Hughes, Alex (Alexandra Capell) (Hughes, Alex (Alexandra Capell). Mindspace Investigations novel., 2014)
Freelancing for the Atlanta PD isn't exactly a secure career; my job's been on the line almost as much as my life. But it's a paycheck, and it keeps me from falling back into the drug habit. Plus, things are looking up with my sometimes-partner, Cherabino, even if she is still simmering over the telepathic Link I created by accident. When my ex, Kara, shows up begging for my help, I find myself heading to the last place I ever expected to set foot in agani--Guild headquarter--to investigate the death of her uncle. Joining that group was a bad idea the first time. Going back when I'm unwanted is downright dangerous. Luckily, the Guild needs me more than they're willing to admit. Kara's uncle was acting strange before he die--crazy strange. In fact, his madness seems to be slowly spreading through the Guild. And when an army of powerful telepaths loses their marbles, suddenly it's a game of life or death....--Amazon.com